Is quantity theory still alive? - Pedro Teles; Harald Uhlig (European Central Bank (ECB), 2013)
This paper investigates whether the quantity theory of money is still alive. We demonstrate three insights. First, for countries with low inflation, the raw relationship between average inflation and the growth rate of money is tenuous at best. Second, the fit markedly improves, when correcting for variation in output growth and the opportunity cost of money, using elasticities implied by theories of Baumol-Tobin and Miller-Orr. Finally, the sample after 1990 shows considerably less inflation variability, worsening the fit of a one-for-one relationship between money growth and inflation, and generates a fairly low elasticity of money demand.
Keywords: E31; E41; E42; E50; 330; inflation targeting; money demand; money demand elasticity; quantity theory; Geldtheorie; Quantitätstheorie; Inflation; Inflationssteuerung; Welt